A Systematic Review of the Psychological Implications of Genetic Testing: A Comparative Analysis Among Cardiovascular, Neurodegenerative and Cancer Diseases - Oliveri, Serena; Ferrari, Federica; Manfrinati, Andrea; Pravettoni, Gabriella (Frontiers in Genetics, 2018)
Background: Genetic test vary in their ability to predict disease occurrence and differ based on the severity of the underlying disease. To date, there are no reports that compare the psychological impact genetic testing may have depending on these differences. Methods: We performed a systematic review of studies that measured the psychological implication of undergoing genetic testing for neurodegenerative disorders, cardiovascular disease, and cancer. Potential eligible articles were systematically searched on PubMed, Google Scholar and PsychInfo and were allocated into three general categories: Cancer (C), Cardiovascular diseases (CV) and Neurodegenerative disorders (N). Results: 47 studies were included, 9 concerning cardiovascular disease, 18 neurodegenerative disorders, and 20 for cancer. Results showed that there are no significant increases in distress and anxiety or adverse impacts on quality of life in subjects who undergo a genetic test for cardiovascular diseases, Alzheimer disease (AD), and cancer susceptibility. Genetic risk for cardiovascular disease is perceived to be manageable because of the existence of screenings and treatments. Genetic analysis for AD is overall experienced as something useful to address the problem with preventive behaviors and accessible channels. In cancer (breast cancer in particular) people feel that they can take control over their lives and direct it as they wish (e.g., surgery vs. screening). Overall, when psychological distress was present, it was related to a full-blown clinical condition in addition to a genetic test result. People tend to consider genetic tests as valid information to take important preventive decisions. Different implications concern Huntington disease, for which several studies revealed the presence or the increase in depressive symptoms, suicidal ideations, and hopelessness in gene carriers. Conclusions: Data suggest that the psychological implications of genetic testing are related to how informative genetic testing is, and depends on personal experience and beliefs about disease. These factors are essential in defining efficient clinical application of gene-testing and to organize personalized care plans.